Uji Efektivitas Gel Ekstrak Buah Tomat (Solanum lycopersicum L.) Terhadap Staphylococcus aureus - Yulia Kristyanti; Evanisia More (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Acne is an inflammatory condition of the sebaceous layer accompanied by blockage and accumulation of keratin, characterized by the appearance of blackheads, papules, pustules, nodules, and cysts, which are considered to damage appearance. In addressing this condition, people tend to use natural remedies because they have fewer side effects. One of the natural ingredients that is often used is tomatoes (Solanum lycopersicum L.). Tomatoes contain many components, including flavonoids, alkaloids, and saponins, which act as antibacterial agents. The purpose of this research is to determine the effectiveness of tomato fruit extract gel as an antibacterial and the most optimal dosage of the tomato fruit extract gel. The method used in this research is the evaluation of the antibacterial ability of tomato fruit extract gel based on organoleptic physical properties, homogeneity, pH, adhesion, spreadability, viscosity, and antibacterial testing of Staphylococcus aureus using the well diffusion method on Mueller Hinton Agar medium. Based on the results of One-Way ANOVA This study shows that 75%, 85%, 95%, and the control (+) tomato fruit extract gel have antibacterial activity. Formula I, with a gel extract concentration of 75%, has an inhibition zone of 18.02 mm, and Formula II, with a gel extract concentration of 85%, has an inhibition zone of 20.84 mm. Both formulas do not have a significant difference. Meanwhile, the gel Formula III with a 95% extract concentration has greater antibacterial activity, measuring 26.65 mm, which is the same as the control (+) or shows no significant difference p>0.05. The most effective dose as an antibacterial is the gel extract of tomato fruit (Solanum lycopersicum L.) with a concentration of 95%, with an inhibition diameter of 26.65 mm, categorized as very strong in inhibiting bacterial growth. Meanwhile, the 75% and 85% concentrations with inhibition diameters of 18.02 mm and 20.84 mm fall into the strong inhibition.